Pro 2 Management Strategy of Radio Republic of Indonesia (RRI) Medan Maintains Millennial Listener Interest in the Era of Broadcasting Digitalization - Anggita, Nadya Dewi; Qarni, Waizul; Inayah, Nurul (Ilomata International Journal of Management, 2024)
Pro 2 Radio Republik Indonesia (RRI) is a central broadcast for young people's creativity. In general, Pro 2 presents information that young people love ranging from lifestyle to the latest music. The AIDDA strategy is a strategy used to maintain the interest of millennial listeners in the era of broadcasting digitalization. In the current era of broadcasting digitalization, radio is faced with the challenge of maintaining the interest of listeners, especially millennials who have many options to access information and entertainment. Pro 2 RRI Medan as one of the radios that targets millennials, needs to implement the right management strategy to maintain the interest of listeners. This study aims to recommend an efficient and effective management strategy for Pro 2 RRI Medan in maintaining the interest of millennial listeners in the era of broadcasting digitalization. In this study, the researcher used a qualitative descriptive analysis technique with the research subjects of informants from Jft. Pranata, broadcasts, young experts, and radio broadcasters. Based on the results of the study, it is explained that the recommendations for strategies that can be done are as follows: Designing and presenting content of broadcast programs that are relevant among millennials. Create programs that can engage listeners. Utilizing social media to promote programs that will be broadcast and to reach millennials who are more active on social media. Ensure good audio quality and Present quality and accurate information, and present information in an interactive way. Create an interesting on-air program and hold off-air activities in the pubic space. Making adjustments in the era of broadcasting digitalization, by providing opportunities for millennials to participate in broadcast programs.